Pendekatan Subjek pada Produksi Program Dokumenter Televisi Bingkai Inspirasi Edisi â€œMenerjang Batas, Sang Disabilitasâ€ - Khoirunnisa, Pipit Amalia; Relawati, Dwi Korina (Jurnal Ilmiah Multimedia dan Komunikasi, 2023)
The creation of television documentary production â€œBingkai Inspirasiâ€ edition of â€œMenerjang Batas, Sang Disabilitasâ€ was motivated by a sense of concern for people with disabilities who are often considered helpless and marginalized from social interactions in society. Triyono is an empowered person with disabilities who succeeded in building Difa Bike, an online motorbike taxi specifically for disabilities to help accessibility of transportation for people with disabilities. The author used observation and interview methods to collect data related to Triyono's life story. To support more in-depth data collection, the author also took a subject approach to the sources persons by combining interpersonal communication and non-verbal communication, through persuasive techniques and passive participant observation. The subject approach to the source persons aims to generate emotional closeness, so that the source persons is more comfortable and confident in telling their life story. The subject approach was successfully applied at every stage of production, thus resulting in a portrait documentary work with a story line, and an interesting visual combination. This work could inspire, motivate and arouse the hearts of the audience.